Molecular phylogeny and taxonomy of Mus pahari (Rodentia: Muridae) - Qingfang Zou; Lin Gu; Tao Zhang; Chengxin Zhou; Xuming Wang; Tong Zhang; Keji Guo; Shaoying Liu; Shunde Chen (Mammalian Biology, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

Enhancing high-solid anaerobic digestion of cattle manure using air nanobubble water: Performance improvements and microbial mechanisms under thermophilic and mesophilic conditions - Ruoyu Wu; Chengxiang Bai; Hailong Shi; Yujie Cao; Cheng Peng; Jiazi Niu; Jie Wang; Jianghe Chen; Qingfang Zhang (Journal of Water Process Engineering, 2026)

Construction of photothermal hydrogel with sunlight internal reflection function for improving solar seawater evaporation efficiency - Shenghua Lv; Ying Chen; Shida Zhao; Wei Liu; Qingfang Zhou; Ruijun Gao (Chemical Engineering Journal, 2026)

Rhodococcus erythropolis KB1 enhances remediation of n-hexadecane pollution by regulating indigenous microbial communities in desert soil - Dan Luo; Siyi Wang; Yanwu Yang; Jianhu Wang; Jixiang Chen; Tianfeng Wang; Yonggang Wang; Qingfang Zhang (Journal of Environmental Chemical Engineering, 2026)

1H NMR guided isolation of flavans from Broussonetia papyrifera and their α-glucosidase inhibitory activity - Tingting Guo; Kepu Huang; Qingfang Wang; Chen Peng; Xingping Zhang; Congxi Gao; Kou Wang; Hongping He; Mingming Li (Phytochemistry, 2026)

Characterization, antioxidant effects of Lycium ruthenicum Murr. Polysaccharides and protective effects against Oxaliplatin-induced peripheral neurotoxicity through inhibition of the RAS – RAF – MEK – ERK signaling pathway - Limei Wen; Taotao Xue; Yali Guo; Yangchen Wang; Qiang Hou; Ruoyu Geng; Chong Ma; Nan Ding; Jinjin Chen; Qingfang Xue; JunPing Hu; Jianhua Yang (Food Research International, 2026)

Monoatomic copper anchored on tubular carbon nitride with high carbon/oxygen abundance via 2-methylimidazole direction: synthesis and catalytic performance - Jianghe Chen; Qingfang Zhang; Xia Zhao; Tianfeng Wang; Yabin Li; Zuoyan Chen; Wenjing Xu; Linhai Yang (Environmental Geochemistry and Health, 2026)

The damaging effects of polyethylene microplastics exposure on juvenile carp and the ameliorative role of Opuntia Milpa alta extract - Yu Sun; Qiurong Zhang; Qingfang Deng; Nima Bai; Huaguo Chen (ENGINEERING Environment, 2026)

Five undescribed 1,3-diphenylpropanes from the leaves of Broussonetia papyrifera - Tingting Guo; Qingfang Wang; Chen Peng; Xingli Zhang; Kepu Huang; Kou Wang; Hongping He; Mingming Li (Phytochemistry Letters, 2025)

Novel oleanolic acid derivatives containing piperazine pyrimidine moieties: design, synthesis, and antimicrobial activity - Fengwei Ma; Qingfang Deng; Yihao Lu; Zhenghong Jia; Su Xu; Qiang Fei; Haijiang Chen; Wenneng Wu (Molecular Diversity, 2025)

Structure-activity relationships and mechanisms of natural polysaccharides in modulating neurological disorders via the microbiota-gut-brain axis - Yulin Song; Qingfang Deng; Jiawen Li; Ruhai Chen; Dan Li; Shenglin Wang; Baitong Jing; Xin Zhou (Carbohydrate Polymers, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Synthesis of tubular amorphous nickel-doped g-C₃N₄ catalyst via pre-assembly strategy for fenton-like oxidation of phenol in wastewater - Qingfang Zhang; Jianghe Chen; Yuxin Zhou; Jianpeng Zhang; Xiangjing Zhang; Tianfeng Wang; Zuoyan Chen; Linhai Yang (Journal of Environmental Chemical Engineering, 2025)

Correction to: Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Inoculations of phosphorus-solubilizing bacteria alter soil properties, microbial communities, and improve crop yield and fruit quality in the tomato production system - Dan Luo; Haizhou Huang; Jianhu Wang; Tianfeng Wang; Qingfang Zhang; Yonggang Wang; Jixiang Chen (Applied Soil Ecology, 2025)

Transcriptome analysis of human spermatozoa with different DNA fragmentation index using RNA sequencing - Kailin Yang; Xue Sun; Qiyuan Zheng; Chen Pan; Siyuan Wang; Qingfang Lu; Changlong Xu; Yangqing Lu (Reproductive Biology, 2024)

The Volcanic Rocks and Hydrocarbon Accumulation in the Offshore Indus Basin, Pakistan - Jing Sun; Jie Liang; Jianming Gong; Jing Liao; Qingfang Zhao; Chen Zhao (Journal of Marine Science and Engineering, 2024)
To analyze the impact of volcanic rocks in the Offshore Indus Basin on hydrocarbon reservoir formation, seismic data interpretation, seismic data inversion, and sea–land correlation analysis were carried out. The results show that, longitudinally, volcanic rocks are mainly distributed at the top of the Cretaceous system or at the bottom of the Paleocene, and carbonate rock platforms or reefs of the Paleocene–Eocene are usually developed on them. On the plane, volcanic rocks are mainly distributed on the Saurashtra High in the southeastern part of the basin. In terms of thickness, the volcanic rocks revealed by drilling in Karachi nearshore are about 70 m thick. We conducted sparse spike inversion for acoustic impedance in the volcanic rock area. The results show that the thickness of the Deccan volcanic rocks in the study area is between 250 and 750 m which is thinning from southeast to northwest. Based on sea–land comparison and comprehensive research, the distribution of volcanic rocks in the Indian Fan Offshore Basin played a constructive role in the Mesozoic oil and gas accumulation in the Indus offshore. Therefore, in the Indian Fan Offshore Basin, attention should be paid to finding Mesozoic self-generated and self-stored hydrocarbon reservoirs and Cenozoic lower-generated and upper-stored hydrocarbon reservoirs.

Harmful effects of microplastics on respiratory system of aquatic animals: A systematic review and meta-analysis - Qiurong Zhang; Xin Zhou; Yu Sun; Qingfang Deng; Qing Wu; Zhirui Wen; Huaguo Chen (Aquatic Toxicology, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Hazards of microplastics exposure to liver function in fishes: A systematic review and meta-analysis - Yu Sun; Qingfang Deng; Qiurong Zhang; Xin Zhou; Ruhai Chen; Siyu Li; Qing Wu; Huaguo Chen (Marine Environmental Research, 2024)

Enhanced lignocellulose degradation and composts fertility of cattle manure and wheat straw composting by Bacillus inoculation - Lingying Wang; Tianfeng Wang; Zhijie Xing; Qingfang Zhang; Xiaohui Niu; Yinshui Yu; Zhijun Teng; Jixiang Chen (Journal of Environmental Chemical Engineering, 2023)

Tissue-resident immune cells in the pathogenesis of multiple sclerosis - Jie Tian; Lingli Jiang; Zixiang Chen; Qingfang Yuan; Chang Liu; Longfeng He; Feng Jiang; Ke Rui (Inflammation Research, 2023)

Ensiling pretreatment fortified with laccase and microbial inoculants enhances biomass preservation and bioethanol production of alfalfa stems - Xueyan Bao; Gang Guo; Wenjie Huo; Qinghong Li; Qingfang Xu; Lei Chen (Science of The Total Environment, 2023)

Microbial respiratory thermal adaptation is regulated by r‐/K‐strategy dominance - Hongyang Chen; Qingfang Jing; Xiang Liu; Xuhui Zhou; Changming Fang; Bo Li; Shurong Zhou; Ming Nie (Ecology Letters, 2022)
Microbial thermal adaptation is considered to be one of the core mechanisms affecting soil carbon cycling. However, the role of microbial community composition in controlling thermal adaptation is poorly understood. Using microbial communities from the rhizosphere and bulk soils in an 8‐year warming experiment as a model, we experimentally demonstrate that respiratory thermal adaptation was much stronger in microbial K ‐strategist‐dominated bulk soils than in microbial r ‐strategist‐dominated rhizosphere soils. Soil carbon availability exerted strong selection on the dominant ecological strategy of the microbial community, indirectly influencing respiratory thermal adaptation. Our findings shed light on the linchpin of the dominant ecological strategy exhibited by the microbial community in determining its respiratory thermal adaptation, with implications for understanding soil carbon losses under warming.

Testicular miRNAs and tsRNAs provide insight into gene regulation during overwintering and reproduction of Onychostoma macrolepis - Guofan Peng; Chao Zhu; Qingfang Sun; Jincan Li; Yining Chen; Yingjie Guo; Hong Ji; Fangxia Yang; Wuzi Dong (Fish Physiology and Biochemistry, 2022)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)

An extracellular oligopeptide permease may be a potential virulence factor of Vibrio harveyi - Qingfang He; Jixiang Chen; Caifeng Li (Journal of Ocean University of China, 2011)

Construction of a molecular functional map of rapeseed (Brassica napus L.) using differentially expressed genes between hybrid and its parents - Yuanyuan Li; Chaozhi Ma; Tingdong Fu; Guangsheng Yang; Jingxing Tu; Qingfang Chen; Tonghua Wang; Xingguo Zhang; Chunyan Li (Euphytica, 2006)

Determination of zinc contents in rabbits with cerebral ischemia by NAA and ICP-AES - Yinsong Wang; Huifang Zhao; Tianxi Zhang; Mingguang Tan; Guisun Zhuang; Baolin Chen; Zongzhi Huang; Hengli Tian; Qingfang Sun (Biological Trace Element Research, 1999)